Maternal areola pH: A chemical basis for mother-infant recognition. (June 2018) - Zanardo, Vincenzo; Volpe, Francesca; Parotto, Matteo; Giliberti, Lara; Simbi, Alphonse; Severino, Lorenzo; Straface, Gianluca
Abstract: Background: The human female's areolar region is the point of arrival of a natural progression from birth to breastfeeding continuum, supported by numerous functional features. Aims: The aim of this study was to look more closely into the areola' skin chemical signals that are uniquely important for mother-infant chemoemission, chemoreception, and breastfeeding continuum. Study design: A dermatological study of the areolae and corresponding breast quadrants was undertaken on 71 healthy, at-term women. Areolar and corresponding breast quadrant pH were assessed pre-partum and 1 and 2 days post-partum using a corneometer (Soft Plus 5.5; Callegari S.P.A., Parma, Italy). Results: Pre-partum, the pH of the areola was significantly higher than the pH of the breast quadrant (4.25 ± 0.26 vs. 4.06 ± 0.44, p < 0.015). Post-partum, the pH of the areola was significantly higher that the pH of the breast quadrant both on day one (4.28 ± 0.31 vs 4.01 ± 0.25, p < 0.001) and on day two (4.39 ± 0.19 vs 4.01 ± 0.16, p < 0.001), respectively. In addition, pre-labor pH of the areola increased on day one post-partum and significantly on day two postpartum (4.25 ± 0.26 vs 4.39 ± 0.19, p 0.004). Moreover, the pH of the areola increased significantly from day one to day two post-partum (4.28 ± 0.31 v s 4.39 ± 0.19, p < 0.041). Conclusions: Our findings show, for the first time, that the areola has a higher pH than the surrounding breast skin, and this increases from day one to day two postpartum. We believe that the pH changes of the areolar region may act as a unique chemical signal to guide the infant directly to the nipple. Highlights: The human female's areolar region is supported by numerous functional features. We found that the areola has a higher pH than the surrounding breast skin, and this increases postpartum. The pH changes of the areolar region may act as a unique chemical signal to guide the infant directly to the nipple.